Calibration-Less DNA Concentration Measurements Using EOF Volumetric Flow and Single Molecule Counting - Farajpour, Nasim; Lastra, Lauren S.; Sharma, Vinay; Freedman, Kevin J. (Frontiers in Nanotechnology, 2021)
Nanopore sensing is a promising tool well suited to capture and detect DNA and other charged single molecules. DNA is a negatively charged biomolecule that can be captured and translocated through a constricted nanopore aperture under an applied electric field. Precise assessment of DNA concentration is of crucial importance in many analytical processes and medical diagnostic applications. Recently, we found that hydrodynamic forces can lead to DNA motion against the electrophoretic force (EPF) at low ionic strength. This study utilized glass nanopores to investigate the DNA capture mechanism and detect DNA molecules due to volumetric flow at these low ionic strength conditions. We measured the DNA capture rate at three different pico-molar concentrations. Our findings indicated that the translocation rate is proportional to the concentration of DNA molecules and requires no calibration since volumetric flow rate and DNA counting directly provides concentration. Using finite element analysis, we calculated the volumetric flow and proposed a simple, straightforward approach for accurate DNA quantification. Furthermore, these experiments explore a unique transport mechanism where one of the most highly charged molecules enters a pore against electric field forces. This quantitative technique has the potential to provide distinct insight into nanopore-based biosensing and further enhance nanopores capability as biomolecule concentration sensors.